3D modeling of an HVDC converter transformer and its application on the electrical field of windings subject to voltage harmonics. (May 2020) - Sun, Weidong; Yang, Lijun; Zare, Firuz; Xia, YanWei; Cheng, Li; Zhou, Kuiyu
Highlights: The voltage harmonics in valve winding of converter transformers are analyzed. An excellent agreement between simulation and measurement is achieved. Electric field is simulated on a 3D converter transformer model. High dV/dt is observed and its influence on partial discharge behavior is analyzed. Abstract: Converter transformers are key facilities in HVDC systems. The operation condition of converter transformers is more complex than that of conventional AC transformers. Because of the superposition of the voltage harmonics, the valve voltage wave is more serrated than a pure AC voltage. As a result, the insulation system withstands severe stress. Several tasks are accomplished in this study to obtain a better understanding of the electrical field distribution in converter transformers as well as analyze the effects of voltage harmonics on the main insulation of converter transformers. First, an HVDC system with a voltage of ±800 kV is simulated and the voltage harmonics at the valve side are obtained. The simulation is verified based on the measurement in a real ±800 kV HVDC substation. The harmonics in valve winding are mainly characterized by components with frequencies of 6k, 12k, 12k ± 1, and 6k ± 1. Then, a full-scaled 3D converter transformer model is proposed. The electric field of the proposed model is calculated under AC, DC, and polarity reversal voltages. Compared with conventional 2D models, the inhomogeneity of the electric field distribution is obtained, and the difference can reach 30%. Finally, the valve voltage waveform is applied on the 3D model to calculate the electric field using finite element method. Results show that the voltage harmonics in valve side further deepen the inhomogeneity of electric field in insulation structures. Moreover, a high value of voltage changing rate ( dV / d t ) with value 2.96 k V / μ s is observed in simulation. The influence of defects on partial discharge within insulation materials under the voltage harmonics is also analyzed.